Pengaruh Harga, Promosi dan Kualitas Pelayanan TerhadapKeputusan Pembelian (Studi Kasus Warung Ayam Ngamok Malang) - Riki Renaldi; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this study was to determine the effect of price, promotion and service quality on purchasing decisions. The independent variables in this study are price, promotion and service quality, while purchasing decisions are the dependent variable. The sample used in this study was 75 respondents. Sampling In this study the sample was saturated, meaning that the entire population was sampled.  the results of the partial analysis, it is obtained a research result which states that price, promotion and service quality influence purchasing decisions, while simultaneously price, promotion and service quality influence purchasing decisions.Keywords: Price, Promotion, Service Quality, Purchasing Decisions